Comparison of Lornoxicam and Fentanyl when added to Lidocaine in Intravenous Regional Anesthesia - (:unkn) unknown (ELSEVIER SCIENCE INC, 2013)
Background and objectives: In this study, our goal was to compare intraoperative and postoperative analgesic effects of lornoxicam and fentanyl when added to lidocaine Intravenous Regional Anesthesia (IVRA) in a group of outpatients who underwent hand surgery. Methods: This is a double blind randomized study. A total of 45 patients were included, randomized into three groups. Patients in Group I (L) received 3 mg.kg(-1) of 2% lidocaine 40 mL; patients in Group II (LL) received 3 mg.kg(-1) lidocaine 38 mL + 2 mL lornoxicam; patients in Group III (LF) received 3 mg.kg(-1) lidocaine 38 mL + 2 mL fentanyl. Our primary outcome was first analgesic requirement time at postoperative period. Results: Lornoxicam added to lidocaine IVRA increased the sensory block recovery time without increasing side effects and increased first analgesic requirement time at the postoperative period when compared to lidocaine IVRA (p < 0.001, p < 0.001 respectively) and fentanyl added to lidocaine IVRA (p < 0.001, p < 0.001 respectively). In addition, we also found that fentanyl decreased tourniquet pain (p < 0.01) when compared to lidocaine but showed similar analgesic effect with lornoxicam (p > 0.05) although VAS scores related to tourniquet pain were lower in fentanyl group. Lornoxicam added to lidocaine IVRA was not superior to lidocaine IVRA in decreasing tourniquet pain. Conclusions: Addition of fentanyl to lidocaine IVRA seems to be superior to lidocaine IVRA and lornoxicam added to lidocaine IVRA groups in decreasing tourniquet pain at the expense of increasing side effects. However, lornoxicam did not increase side effects while providing intraoperative and postoperative analgesia. Therefore, lornoxicam could be more appropriate for clinical use. (C) 2013 Sociedade Brasileira de Anestesiologia. Published by Elsevier Editora Ltda. All rights reserved.
Keywords: Anesthesia, Conduction; Anesthetics, Local; Fentanyl; Lidocaine; Piroxicam/lornoxicam; PRILOCAINE; ANALGESIA; KETOROLAC; MORPHINE; BLOCK; HAND